Fazendo conexões com o mundo real: uso de conceitos e modelos da física no contexto da zoologia - Shiguematu, Camila Akemi Nakamura [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
There are considerations of that the education of Physics of the way as comes being driven us textbooks and consequently in classroom, is distant and distorted of their real purpose. We notice that the education of this science through the Physical school discipline, has I assume a character of preparation for university entrance exams exercises resolution, exceling for the memorization of formulae and by the mathematical solutions, fact that looks to cause to it is lacking of motivation and to the disinterest of the students regarding his contents. Since we are surrounded by phenomena, events, elements of the nature, new technologies, objects and so many others that can be explained and many times until applied and/or reproduced by means of physical concepts, there is no reason for treat to Physical as somewhat academic and remote of the reality. The little interest of high school students by the discipline of Physics and their poor performance in the learning of his contents has led to the search of new paths, resources and strategies that promote a more meaningful learning. Taking into account these facts, we seek in this course conclusion work, observe, analyze and apply concepts of the Physical one in multiple elements of ours routine, doing use of the interdisciplinary nature as a possible mechanism. The animals exert a fascination on most people. Much of what we see in their way of being and behaving can be explained by the laws of Physics and its models. Their physique, behavior and activities involve diverse movements, communication and sensing as physical limitations varied. Zoologists and physicists build models in an attempt to explain or understand animal behavior using well-established physical principles. The creation of physical models is going to approach a problem, identifies the fundamental information and removing all of the irrelevant details. An example... (Complete abstract click electrnic access below)

Há considerações de que o ensino de Física da maneira como vem sendo conduzido nos livros didáticos e consequentemente em sala de aula, está distanciado e distorcido de seu real propósito. Notamos que o ensino desta ciência através da disciplina escolar Física, tem assumido um caráter de preparação para resolução de exercícios de vestibulares, primando pela memorização de fórmulas e pelas soluções matemáticas, fato que parece levar à desmotivação e ao desinteresse dos alunos com relação aos seus conteúdos. Uma vez que estamos rodeados por fenômenos, acontecimentos, elementos da natureza, novas tecnologias, objetos e tantos outros que podem ser explicados e muitas vezes até aplicados e/ou reproduzidos por meio de conceitos físicos, não há razão para se tratar a Física como algo acadêmico-teórico e afastado da realidade. O pouco interesse dos alunos do ensino médio pela disciplina de Física e o baixo desempenho na aprendizagem de seus conteúdos tem levado à busca de novos caminhos, recursos e estratégias que promovam uma aprendizagem mais significativa. Levando em conta estes fatos, buscamos neste trabalho de conclusão de curso, observar, analisar e aplicar conceitos da Física em múltiplos elementos do nosso cotidiano, fazendo uso da interdisciplinaridade como um possível mecanismo. Os animais exercem fascínio sobre a maioria das pessoas. Muito do que observamos em sua maneira de ser e se comportar pode ser explicado por leis e modelos da Física. Sua constituição física, seu comportamento e atividades envolvem tanto diversidade de movimentos, comunicação e sensoriamento como limitações físicas variadas. Físicos e zoólogos constroem modelos na tentativa de explicar ou entender o comportamento animal usando princípios físicos bem estabelecidos. A criação de modelos físicos tenta abordar um problema, identifica as informações... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Física - Estudo e ensino; Sistemas biologicos; Livros didáticos; Zoologia; Biomimetismo; Physics - Study and teaching; Biological systems; Biomimetics